Manajemen Laboratorium Seni Rupa dan Desain yang Berkelanjutan : Studi Kasus Universitas Negeri Gorontalo - Hasniyati Balise; Restu Lanjari; Rahina Nugrahani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This research is to find out the laboratory management at the Department of Fine Arts and Design, Faculty of Engineering, Gorontalo State University. This research covers several aspects, namely the type of laboratory management, laboratory management procedures, and standard operating procedures for laboratory use. This research uses a qualitative method. Data collection was carried out through three methods, namely observation, interviews, and documentation. Data analysis is carried out in three steps, namely data reduction, data presentation, and conclusion drawn. The results of this study show that: 1) laboratory management procedures are carried out in several stages, namely planning, structuring, administration, security, maintenance, and supervision; 2) standard operating procedures for using laboratories include several things, such as laboratory services, borrowing procedures, laboratory use, equipment borrowing procedures, material use procedures, and tool use procedures. From the results of the study, it can be concluded that the laboratory management of the Department of Fine Arts and Design, Faculty of Engineering, Gorontalo State University has been running well. However, there are several aspects that still need to be developed, such as the completeness of the type of laboratory, the number of equipment, the upgrade of equipment, and the addition of materials that are in accordance with the needs of the amount or volume of use.